Cyclophosphamide modulated the foreign body inflammatory reaction in tilapia (Oreochromis niloticus). Issue 107 (December 2020) - Charlie-Silva, Ives; Conde, Gabriel; Mendonça Gomes, Juliana Moreira; Johnny da Rosa Prado, Ed; Fernandes, Dayanne Carla; Cristina de Moraes, Alessandra; Eto, Silas Fernandes; Conceição, Katia; Antonio de Andrade Belo, Marco
Abstract: In order to understand events and mechanisms present in the pathophysiology of tilapia's chronic inflammation and based on the immunomodulatory activity attributed to cyclophosphamide which is widely used to suppress immune responses in human medicine, the present study investigated the effects of cyclophosphamide (CYP) treatment on the modulation of foreign body inflammatory reaction in Nile tilapia ( Oreochromis niloticus ) with round glass coverslip implanted in the subcutaneous tissue (9 mm of diameter). Forty tilapia (151 ± 10, 2 g) were randomly distributed in 5 aquariums (n = 8) with a capacity of 250 L of water each, to compose two treatments (sampled 3 and 6 days post-implantation): implanted/untreated (control) and implanted/treated with 200 mg of CYP kg −1 of b.w., through i.p. route. A fifth group (n = 8) was sampled without any stimulus (naive) to obtain reference values. CYP-treated tilapia showed decrease in macrophage accumulation, giant cell formation and Langhans cells on the glass coverslip when compared to control fish. The treatment with CYP resulted in decrease of leukocyte and thrombocyte counts. Decrease in alpha-2-macroglobulin, ceruloplasmin, albumin and transferrin levels, as well as increase in haptoglobin, complement C3 and apolipoprotein A1 were observed in tilapias during foreign body inflammation. Blood levels of complement C3, alpha-2-macroglobulin, ceruloplasmin and transferrin were modulated by treatment with CYP. Therefore, the treatment with 200 mg of CYP kg −1 of b.w. in tilapia resulted in an anti-inflammatory effect by suppressing the dynamics between leukocytes in the bloodstream and macrophage accumulation with giant cell formation in the inflamed focus, as well as by modulating APPs during foreign body reaction. Graphical abstract: Image 1 Highlights: Anti-inflammatory effect was observed in CYP-treated tilapia. Tilapia presented modulation of APPs during foreign body reaction. Treatment with CYP suppressed macrophage accumulation and polykarion formation. Tilapia treated with CYP showed decrease of leukocyte and thrombocyte counts. Alpha-2-macroglobulin, ceruloplasmin and transferrin were modulated by CYP.